Yellow Stripe1. Expanded Roles for the Maize Iron-Phytosiderophore Transporter - Roberts, Louis A. (American Society of Plant Biologists, 2004)
Graminaceous monocots, including most of the world's staple grains (i.e. rice, corn, and wheat) use a chelation strategy (Strategy II) for primary acquisition of iron from the soil. Strategy II plants secrete phytosiderophores (PS), compounds of the mugineic acid family that form stable Fe(III) chelates in soil. Uptake of iron-PS chelates, which occurs through specific transporters at the root surface, thus represents the primary route of iron entry into Strategy II plants. The gene Yellow stripe1 (Ys1) encodes the Fe(III)-PS transporter of maize (Zea mays). Here the physiological functions performed by maize YS1 were further defined by examining the pattern of Ys1 mRNA and protein accumulation and by defining YS1 transport specificity in detail. YS1 is able to translocate iron that is bound either by PS or by the related compound, nicotianamine; thus, the role of YS1 may be to transport either of these complexes. Ys1 expression at both the mRNA and protein levels responds rapidly to changes in iron availability but is not strongly affected by limitation of copper or zinc. Our data provide no support for the idea that YS1 is a transporter of zinc-PS, based on YS1 biochemical activity and Ys1 mRNA expression patterns in response to zinc deficiency. YS1 is capable of transporting copper-PS, but expression data suggest that the copper-PS uptake has limited significance in primary uptake of copper.